2018
DOI: 10.9734/jesbs/2018/40740
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Community towards Female Genital Mutilation in Manyoni District, Singida Region, Tanzania

Abstract: The female genital mutilation (FGM) has a series of consequences which most of them lead to discomfort, maternity complications and finally deaths of girls and women. In Tanzania as well as other countries, a number of campaigns have been waged against FGM, but to date the practice still persists. This problem requires critical researches to look for the factors leading to the FGM not to end. Therefore, this study intended to assess the attitudes of people towards the FGM and its social value in order to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Even when one of the family members gets sick, women are more concerned in providing health services. Studies by Waheke (2015) and Chingonikaya et al (2018) reported that FHHHs have fewer chances of participating in community organisations because most of HHs is headed by males who take liabilities of participating in those organisations whose membership unit is the household. Women believe that by so doing they may be socially accepted and protect their marriages.…”
Section: Socio-demographic Characteristics Of Respondentsmentioning
confidence: 99%
“…Even when one of the family members gets sick, women are more concerned in providing health services. Studies by Waheke (2015) and Chingonikaya et al (2018) reported that FHHHs have fewer chances of participating in community organisations because most of HHs is headed by males who take liabilities of participating in those organisations whose membership unit is the household. Women believe that by so doing they may be socially accepted and protect their marriages.…”
Section: Socio-demographic Characteristics Of Respondentsmentioning
confidence: 99%
“…The experience shows that European countries promoted health care systems such that their people's life expectancies are relatively high compared to the rest of the countries in the world (Martin, 2017). The adoption of Community Health Insurance depends much on community attitudes on particular types of insurance as reported by Chingonikaya et al (2018) that attitude may influence the behaviour change of someone as it is a relatively enduring organization of beliefs, and behavioural tendencies towards socially significant objects, groups, events or symbols.…”
Section: Introductionmentioning
confidence: 99%